(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study aims to investigate the factors influencing the purchasing behavior of cosmetic products among male consumers in Tirunelveli district. By employing both primary and secondary data collection methods, the research seeks to identify the key determinants of cosmetic product purchase decisions and the primary reasons for male cosmetic usage in the region. A sample of 150 male respondents will be surveyed to gather empirical data on their cosmetic consumption patterns, preferences, and the underlying motivations. The structured questionnaire is prepared and distributed to the respondents located in the Tirunelveli region. The findings of this study will contribute to a better understanding of the male cosmetic market in Tirunelveli, providing valuable insights for marketers and businesses to develop effective strategies tailored to the specific needs and preferences of male consumers.